2020
DOI: 10.1242/dev.181495
|View full text |Cite
|
Sign up to set email alerts
|

Stochasticity and determinism in cell fate decisions

Abstract: During development, cells need to make decisions about their fate in order to ensure that the correct numbers and types of cells are established at the correct time and place in the embryo. Such cell fate decisions are often classified as deterministic or stochastic. However, although these terms are clearly defined in a mathematical sense, they are sometimes used ambiguously in biological contexts. Here, we provide some suggestions on how to clarify the definitions and usage of the terms stochastic and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 69 publications
1
46
0
Order By: Relevance
“…The advance of imaging techniques, image analysis algorithms, and the possibility of performing backtracking studies in the retina are exciting emerging tools to follow similar questions in future studies. Such sophisticated studies will in turn promote our understanding of reproducibility and/or plasticity of lineage decisions at diverse developmental stages in different tissues of the CNS ( Zechner et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The advance of imaging techniques, image analysis algorithms, and the possibility of performing backtracking studies in the retina are exciting emerging tools to follow similar questions in future studies. Such sophisticated studies will in turn promote our understanding of reproducibility and/or plasticity of lineage decisions at diverse developmental stages in different tissues of the CNS ( Zechner et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Computational and experimental approaches have been used to study stochasticity in biological systems (Meyer and Roeder 2014 ). For example, a recent review on stochasticity in cellular fate decisions compared it to a weighted coin toss (Zechner et al 2020 ). We have now begun to understand the mechanisms underlying the figurative coin toss model and to identify the factors contributing to the associated coin weights in various developmental processes.…”
Section: Stochasticity In Plant Developmentmentioning
confidence: 99%
“…Variability in gene expression is not the only source of phenotypic variations. Examples from animals have shown that mechanical properties of cells and molecular fluctuations in the dynamics of signaling pathways affect cellular fate decision (Kroll et al 2020 ; Weinreb et al 2020 ; Zechner et al 2020 ). Significant advancements have been made in research on stochasticity in cellular size and patterning (Meyer and Roeder 2014 ).…”
Section: Stochasticity In Plant Developmentmentioning
confidence: 99%
“…Heterogeneity in cell populations may originate from deterministic or stochastic processes. For example, the observed distribution of cell cycle durations in a population of cells is governed either by stochastic processes, inherited in a deterministic fashion, or some combination of both [3][4][5][6] (Figure 1A). Previous studies have shown poor correlations within lineages when observing direct ancestral relationships, but remain correlated with immediate relatives 4,7,8 .…”
Section: Introductionmentioning
confidence: 99%